Malu Sensitivity and the Identities of Non- Heteronormative Malay Muslim Men in Peninsular Malaysia - Chua Hang-Kuen (Kajian Malaysia, 2019)
Apart from Islamic heteronormativity, malu (shame) sensitivity remains a significant cultural code of conduct in informing Malays’ social relations and sexualities in public domains. Yet it remains obscure as how malu operates in the mundane lives and governs the identities of non-heteronormative Malay Muslim men in Malay Peninsula. The narrations examined here illuminate the social dynamics of malu sensitivity and how navigating these social dynamics inhibits and permits the expressions of non-heteronormative identities in public. It is concluded that the expressions of their non-heteronormative identities lie between conforming to and resisting the tacit Rousseauian social contract circumscribed by malu sensitivity and Islamic heteronormativity. On the one hand, they have to conform to the tacit social contract and restrain their non-heteronormativities. On the other hand, they capitalise on social tolerance and Islamic sex segregation, draw on gay liberalism discourse, and rely on tactful navigating strategies to resist the social conventions. As a result, their identities become diverse, ambiguous, fragmented and depoliticised.